2007
DOI: 10.1073/pnas.0700041104
|View full text |Cite
|
Sign up to set email alerts
|

Induced-fit tightens pleuromutilins binding to ribosomes and remote interactions enable their selectivity

Abstract: antibiotics ͉ functional flexibility ͉ ribosome crystallography ͉ peptidyl transferase center ͉ retapamulin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
167
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 53 publications
10
167
1
5
Order By: Relevance
“…In the SA50S-BC3205 crystal structure, BC-3205 is bound at the PTC, so that the tricyclic mutilin core is blocking the A-site, and its C14 extension is pointing into the P-site, thus perturbing A-and P-site tRNA accommodation, as was seen in the ribosome-pleuromutilin complexes with D50S (35,36). In the SA50S-BC3205 complex, the conformation of the flexible nucleotide U2585 is different from that of the unbound SA50S, and its conformational range is reduced because of partial overlap by the BC-3205 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SA50S-BC3205 crystal structure, BC-3205 is bound at the PTC, so that the tricyclic mutilin core is blocking the A-site, and its C14 extension is pointing into the P-site, thus perturbing A-and P-site tRNA accommodation, as was seen in the ribosome-pleuromutilin complexes with D50S (35,36). In the SA50S-BC3205 complex, the conformation of the flexible nucleotide U2585 is different from that of the unbound SA50S, and its conformational range is reduced because of partial overlap by the BC-3205 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, their cores are placed in a similar fashion at the A-site and their C14 extensions are pointing toward the P-site; thus, they directly inhibit peptide bond formation. Because the PTC is almost fully conserved, the clinical efficacy of the pleuromutilins stems from their efficient inhibitory modes, which are attained by structural diversity in the second or third shells around the PTC, by exploiting the ribosomal intrinsic functional flexibility for induced fit and remote conformational rearrangements that result in a tightening up of the binding pockets (35,36).…”
mentioning
confidence: 99%
“…Additionally, similar to pleuromutilins that utilize a network of remote interactions, LC binding is influenced by the second-shell nucleotides, specifically G2576, A2062, C2530, U2531, C2507, U2584, G2581, C2610, and A2059. Thus, LC exploits the PTC's inherent flexibility for achieving high binding affinity (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic studies performed over the last decade revealed the exact binding sites of a variety of such drugs (see refs.1 and 2 for review). Many natural antibiotics, as well as their clinically relevant semisynthetic derivatives, bind at the peptidyl transferase center (PTC) in the large ribosomal subunit (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Most of these compounds inhibit cell growth by interfering with peptide bond formation (15).…”
mentioning
confidence: 99%
“…On the other hand, the same binding pockets may accommodate chemically different antibiotics. Similarly, the nature of seemingly identical mechanisms of drug resistance is dominated, directly or via cellular effects, by the antibiotics' chemical properties (Davidovich et al 2007. The observed variability in antibioticbinding and inhibitory modes justifies expectations for structurally based improved properties of existing compounds as well as for the discovery of novel drug classes.…”
Section: From In-house X-ray Generators To Advanced Synchrotron Radiamentioning
confidence: 99%